1995
DOI: 10.1021/np50122a014
|View full text |Cite
|
Sign up to set email alerts
|

New Steroidal Glycosides from Mimusops elengi

Abstract: T wo new steroidal glycosides [1 and 2] have been isolated from Mimusops elengi and characterized as the 3-0-3-D-glucopyranoside and the 3-0-ß-D-galactopyranoside of (24R)stigmast-7,22(£)-dien-3ot-ol, respectively.The genus Mimusops belongs to the family Sapotaceae and comprises 30 species, of which three, including M. elengi L., are indigenous to Pakistan. . elengi is an ornamental tree with sweet-scented flowers. The bark and fruit of this plant are used in the treatment of diarrhea and dysentery, and a deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…The spectrometric analysis of CfC2F5 showed the presence of stigmast-7,22-dien-3-ol and stigmast-7-en-3-ol, respectively (Table1). The chemical structure of these phytosterols was confirmed by 1 H and 13 C NMR (Jahan et al, 1995;Seo et al, 1987). The CfC1F2 fraction (1.7 g) was again fractionated on a RP-18 silica gel column (10 g, 230-400 mesh, POLYGOPREP C18, Macherey-Nagel, Pennsylvania, USA), eluted with a gradient system of water: acetonitrile to give 49 fractions (CfC3F1-CfC3F49).…”
Section: Isolation and Identification Of Major Compounds From C Ficimentioning
confidence: 99%
“…The spectrometric analysis of CfC2F5 showed the presence of stigmast-7,22-dien-3-ol and stigmast-7-en-3-ol, respectively (Table1). The chemical structure of these phytosterols was confirmed by 1 H and 13 C NMR (Jahan et al, 1995;Seo et al, 1987). The CfC1F2 fraction (1.7 g) was again fractionated on a RP-18 silica gel column (10 g, 230-400 mesh, POLYGOPREP C18, Macherey-Nagel, Pennsylvania, USA), eluted with a gradient system of water: acetonitrile to give 49 fractions (CfC3F1-CfC3F49).…”
Section: Isolation and Identification Of Major Compounds From C Ficimentioning
confidence: 99%
“…[25] Several triterpenoids, steroids, steroidal glycosides, flavonoids, and alkaloids have been reported from this species. [25][26] The phytochemical review indicated the presence of taraxerol, taraxerone, ursolic acid, [27][28] betulinic acid, V-spinosterol, W-sitosterol, lupeol, [27][28] alkaloid isoretronecyl tiglate [29] and mixture of triterpenoid saponins in the bark of Mimusops elengi. In vitro free radical scavenging activity of methanol extract of the leaves of M. elengi was reported [30] in the literature.…”
Section: Preparation Of the Extractmentioning
confidence: 92%
“…[24] The bark and fruit of this plant are used in the treatment of diarrhea and dysentery, and a decoction of the bark is used as a gargle. [25] The pounded seeds pasted with oil are used for the treatment of obstinate constipation. Pillow stuffing made from the dried flowers induces nasal discharge and relieves headache.…”
Section: Preparation Of the Extractmentioning
confidence: 99%
“…The more polar fractions were purified by Sephadex LH-20 and RP-18 C.C., eluted with MeOH-H 2 O (90:10 and 85:15) to yield 1 (300 mg) and 2 (250 mg). The sugar residues as TMS derivative were identified by GC analysis using suitable sugar standard after acid hydrolysis [3] of the natural products.…”
Section: Introductionmentioning
confidence: 99%